Non-Woody Tongue Actinobacillosis In A Cow: A Rare Manifestation (Applied Biological Research, 2016)
Actinobacillosis is an infectious disease caused by a Gram-negative coccobacilli, Actinobacillus  lignieresii, reported world widely often as affecting the soft tissues especially tongue of cattle and  sheep (Dirksen et al., 2005; Radostits et al., 2007). A. lignieresii is a commensal of upper digestive  tract of ruminants. Traumatic erosion, ulcer and penetrating lesion induced by hard fibrous feed  causes a breach in skin barrier integrity and can establish an infection (Brown et al., 2007; Smith,  2009). In cattle, the classical presentation of infection is woody tongue, but also soft tissues like  lymph nodes (retropharyngeal and submandibular) and other tissues of the head, pharynx, chest,  flank, stomach, omentum and limbs can be affected (Radostits et al., 2007; Taghipour-Bazargani et  al., 2010). Grossly, Actinobacillosis is characterized by the presence of granulomas with purulent  discharges characteristically containing ‘sulphur’ granules. Microscopically, pyogranulomas with  Splendore-Hoepelli phenomenon surrounded by fibrosis after acute local inflammation are the most  common features. The present case describes the clinical manifestations, bacteriologic, gross and  histo-pathologic characteristics of an unusual manifestation of actinobacillosis in a cow.
Keywords: Non-Woody; Actinobacillosis; Manifestation